Pengaruh Budaya Organisasi, Disiplin Keja dan Kompensasi terhadap Kepuasan Kerja serta dampaknya pada Kinerja Karyawan PT. Tiga Daun Kapuas - Muspiron Muspiron; Hairudinor Hairudinor; Agus Febrianto (JURNAL BISNIS DAN PEMBANGUNAN, 2020)
Organizations are formed to achieve a certain goal that has been set before, because basically the organization is a form of union of humans to achieve a common goal in which there are activities, therefore the organization needs to have qualified employees and have high enthusiasm and loyalty. Lately, many organizations or companies, both social or business organizations, face problems with human resources. Companies that face human resource problems can be overcome if the company has a good organizational culture, work discipline and compensation that is appropriate for employees.This study aims to examine the effect of Organizational Culture (X1), Keja Discipline (X2) and Compensation (X3) on Job Satisfaction (Z) and its impact on Employee Performance (Y) at PT. Three Kapuas Leaves. The sample was taken as many as 65 employees using a saturated sampling technique. Data collection using a questionnaire while data analysis using SPSS version 2.0 SmartPLS Analysis.The test results prove that Organizational Culture (X1) has a significant effect on Job Satisfaction (Z) with a significant effect of 28,21%, Organizational Culture (X1) has a significant effect on Employee Performance (Y) with a influence of 33,89%, Work Discipline (X2) has a significant effect on Satisfaction Work (Z) with an effect of 33,11%, Work Discipline (X2) has a significant effect on Employee Performance (Y) with a magnitude of 34,09%, Compensation (X3) has a significant effect on Job Satisfaction (Z) with a magnitude of 22,21%, Compensation (X3 ) significant effect on Employee Performance (Y) with a magnitude of influence 16,47% and Job Satisfaction (Z) have a significant effect on Employee Performance (Y) with a magnitude of 7,6%.Keywords : Organizational Culture, Work Discipline, Compensation, Job Satisfaction and Employee performance